An assessment of the potential compensation provided by the new ‘National Living Wage’ for the personal tax and benefit measures announced for implementation in the current parliament. ([2015]) - Elming, William; Emmerson, Carl; Johnson, Paul, 1967-; Phillips, David, 1985-
No abstract available